DEVELOPMENT MODEL MANAGEMENT WASTE BANK VILLAGERS WEST SEMPLAK - Lestari, A (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Real Working Lecture (KKN) is shown to the student Forms of Devotion society which is the language of prayer one embodiment Forms Tri Dharma College. KKN demanding activities require students to be able to solve problems that occur in the community, developing the potential that exists somewhere either from natural resources and human resources, help build a place to be more advanced than before by studying and working in a certain time. KKN students participating in the Faculty of Education University of Djuanda empower people Semplak West Village with a basis to develop models of waste bank management. The waste problem is still a staple of the customs surrounding communities. The garbage disposal is not in place result in the environment becomes uncomfortable and also can be a field of disease. With the garbage bank as the work program KKN the Faculty of Education is expected to villagers in Semplak West could change bad habits for the better by saving garbage and befriending the trash, not only to make an economic value, but it has a noble purpose, namely to make the environment clean, healthy and comfortable, because a healthy environment not only for others but feel for ourselves.